The food dye Tartrazine disrupts vascular formation both in zebrafish larvae and in human primary endothelial cells - Dinh Duy Thanh; Nguyen Bich-Ngoc; Cécile Paques; Aurélie Christian; Stéphanie Herkenne; Ingrid Struman; Marc Muller (Scientific Reports)
Abstract Tartrazine (E102) is a controversial coloring agent whose potential impacts on human health are not fully understood. Our study reveals the vascular disrupting effects of tartrazine (TTZ) on developing zebrafish embryos in vivo and on human umbilical vein endothelial cells in vitro. The dye was shown to cause dose-dependent hemorrhages in zebrafish embryos. Analyzing transgenic zebrafish harboring fluorescent endothelial cells revealed that TTZ treatment disrupted cell organization into vessels in both the sub-intestinal vein and the brain area. Assays on human umbilical vein endothelial cells demonstrated that TTZ inhibited endothelial proliferation, tube formation, and migration in a dose-dependent manner. Taken together, our results indicate for the first time that TTZ can affect endothelial cell properties, possibly by disrupting Rho family GTPase pathways which control the cytoskeleton. Our finding provides a credible explanation for many reported human health impacts and offers prospective applications for biomedicine.